Konsep Model Example Non Example Relevansinya dengan Pembelajaran Tematik Bagi Siswa Madrasah Ibtidaiyah - Feti Siti Fatimah (HMPS PGMI FTIK IAIN Jember, 2022)
The purpose of this study was to determine: 1) to find out the application of the example non example model in research, 2) to find out thematic learning process in madrasah ibtidaiyah, 3) to find out relevance of example non example model with thematic learning for madrasah ibtidaiyah students. The method used in this research is library research. Data analysis used in qualitative thesis. Qualitative analysis has four methods, namely domain analysis, taxonomic, comparative, and cultural theme analysis, however the researcher will only discuss three methods, namely: domain analysis, taxonomy, and cultural theme analysis. The result of study show that the example non example model has relevance to thematic learnig for madrasah ibtidaiyah students, including: 1) the example non example model is learning model that provides innovation in teaching and learning activities. In thematic learning, education is to develop active students in the learning process. 2) the purpose of the example non example makes it easier for students to choose one picture between the two options that are approriate according to the subject matter. Thematic learning objectives students can feel the benefits and meanings that exist in the material related to their lives. 3) the example non example model places students as subjects who are more active in the learning process, while the role of educators is as a facilitator, guide, dynamist, mediator, and motivator. 4) thematic learning places students at the center of teaching and learning activities, while the role of educators is as a facilitator, guide, motivator, and dynamist. Tujuan penelitian ini untuk mengetahui: 1) Untuk mengetahui penerapan model example non example dalam penelitian, 2) proses pembelajaran tematik di madrasah ibtidaiyah, 3) Relevansi model example non example dengan pembelajaran tematik bagi siswa madrasah ibtidaiyah. Metode yang digunakan dalam penelitian ini adalah penelitian pustaka (libraryresearch). Analisis data yang digunakan dalam skripsi kualitatif. Analisis kualitatif mempunyai empat metode yaitu analisis domain, taksonomi, kompensial, dan analisis tema kultural, akan tetapi peneliti hanya akan membahas tiga metode saja yaitu: analisis domain, taksonomi, dan analisis tema kultural. Hasil penelitian menunjukan model example non example mempunyai relevansi terhadap pembelajaran tematik bagi siswa madrasah ibtidaiyah, diantaranya: 1) Model example non example salah satu model pembelajaran yang memberikan inovasi dalam kegiatan belajar dan mengajar. Dalam pembelajaran tematik, pendidikan untuk mengembangkan peserta didik aktif dalam proses pembelajaran. 2) Tujuan model example non example memudahkan siswa dapat memilih satu gambar antara dua pilihan yang ada dengan tepat sesuai materi pelajaran. Tujuan pembelajaran tematik siswa dapat merasakan manfaat dan makna yang ada dalam materi yang berkaitan dengan kehidupan mereka. 3) Model example non example menempatkan peserta didik sebagai subjek yang lebih aktif dalam proses pembelajaran , sedangkan peran pendidik sebagai fasilitator, pembimbing, dinamisator, mediator, dan motivator. 4) Pembelajaran tematik menempatkan peserta didik sebagai pusat dalam kegiatan belajar mengajar, sedangkan peran pendidik sebagai fasilitator, pembimbing, motivator, dan dinamisator.